Age and active navigation effects on episodic memory: A virtual reality study. (28th February 2015) - Sauzéon, Hélène; N'Kaoua, Bernard; Arvind Pala, Prashant; Taillade, Mathieu; Guitton, Pascal
Abstract : We investigated the navigation‐related age effects on learning, proactive interference semantic clustering, recognition hits, and false recognitions in a naturalistic situation using a virtual apartment‐based task. We also examined the neuropsychological correlates (executive functioning [EF] and episodic memory) of navigation‐related age effects on memory. Younger and older adults either actively navigated or passively followed the computer‐guided tour of an apartment. The results indicated that active navigation increased recognition hits compared with passive navigation, but it did not influence other memory measures (learning, proactive interference, and semantic clustering) to a similar extent in either age group. Furthermore, active navigation helped to reduce false recognitions in younger adults but increased those made by older adults. This differential effect of active navigation for younger and older adults was accounted for by EF score. Like for the subject‐performed task effects, the effects from the navigation manipulation were well accounted for by item‐specific/relational processing distinction, and they were also consistent with a source monitoring deficit in older adults.